Can e-TEP be a Better Option than TEP for Inguinal Hernia Repair? - Hossain, Mohammad Monir; Rahman, Shah Raihanur; Hossain, Delowar (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: An organ or fatty tissue, like the colon, might abnormally emerge through the wall of the cavity in which it normally resides, for making a hernia. Among different hernias inguinal hernia repair is the most frequently done procedures by surgeons in Bangladesh and worldwide. Now-a-days Laparoscopic repair is performed in this country and accepted by the people. Laparoscopic TEP and e-TEP are excellent procedure for repair of inguinal hernia. In this Centre, we performed both procedures. In Technical aspects e-TEP is better approachable than TEP. Objective: In this article we present how to overcome the difficulties of TEP technique by doing the enhanced view totally extra peritoneal technique for repair of inguinal hernia. Methods: It is a non-randomized comparative study. The study consists of patients with laparoscopic hernioplasty for the period of one year (From July 2018 to July 2019). Total 20 cases were included in the study (10 cases of Laparoscopic e-TEP and 10 cases of Laparoscopic TEP). Data were collected by follow up visit, questionnaire and by phone call. Results: The study consists of 20 patients among whom 10 were placed in group A (e-TEP group) and 10 cases were placed in group B (TEP group). Mean operating time in group A was 108.5 min while in group B was 114 min. Pain scoring in group A was 75% and giving score 1-2 (mild pain). All are male. Mean age for e-TEP was 26.5 years and for TEP was 35.6 years. Conclusion: Laparoscopic e-TEP provides wide area than TEP for repair of inguinal hernia. It is a surgeon friendly procedure for repairing hernia. It is easier to learn e-TEP than TEP. JAFMC Bangladesh, Vol 19, No 2 (December) 2023: 21-23